2016
DOI: 10.1016/j.expneurol.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophosphorylation of tau at S422 enhances SDS-stable dimer formation and impairs both anterograde and retrograde fast axonal transport

Abstract: In Alzheimer's disease (AD), tau undergoes numerous modifications, including increased phosphorylation at serine-422 (pS422). In the human brain, pS422 tau protein is found in prodromal AD, correlates well with cognitive decline and neuropil thread pathology, and appears associated with increased oligomer formation and exposure of the N-terminal phosphatase-activating domain (PAD). However, whether S422E phosphorylation contributes to toxic mechanisms associated with disease-related forms of tau remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 79 publications
4
47
0
Order By: Relevance
“…While these potential regulatory events are not well understood, phosphorylation is important in modulating tau conformations. Previous studies have shown that pseudophosphorylation at the AT8 site alters tau folding (Jeganathan, et al, 2008) and significantly impairs anterograde FAT as a monomeric protein (Kanaan, et al, 2011), and more recently we found that pseudophosphorylation at Ser 422 similarly impairs anterograde transport as a monomer and is toxic to retrograde transport when aggregated (Tiernan, et al, 2016). Conversely, phosphorylation of tyrosine 18 within PAD appears to mitigate the deleterious effects of pathological forms of tau (Kanaan, et al, 2012), and might be involved in the normal regulation of PAD-dependent effects on transport (Kanaan, et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…While these potential regulatory events are not well understood, phosphorylation is important in modulating tau conformations. Previous studies have shown that pseudophosphorylation at the AT8 site alters tau folding (Jeganathan, et al, 2008) and significantly impairs anterograde FAT as a monomeric protein (Kanaan, et al, 2011), and more recently we found that pseudophosphorylation at Ser 422 similarly impairs anterograde transport as a monomer and is toxic to retrograde transport when aggregated (Tiernan, et al, 2016). Conversely, phosphorylation of tyrosine 18 within PAD appears to mitigate the deleterious effects of pathological forms of tau (Kanaan, et al, 2012), and might be involved in the normal regulation of PAD-dependent effects on transport (Kanaan, et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
“…The recent development of tau antibodies that detect PAD exposure (Combs, et al, 2016,Kanaan, et al, 2011) or oligomeric species (Castillo-Carranza, et al, 2014b,Lasagna-Reeves, et al, 2012,Patterson, et al, 2011a,Ward, et al, 2013) has facilitated additional insight into the pathological conformations adopted by tau. More recently, we showed that several disease-related modifications of tau cause conformational display of the PAD in the amino terminus of tau and oligomeric tau aggregates impaired axonal transport confirming a link between pathological conformations and tau toxicity (Kanaan, et al, 2011,LaPointe, et al, 2009,Patterson, et al, 2011a,Patterson, et al, 2011b,Tiernan, et al, 2016). Moreover, many other studies suggest oligomeric tau is toxic to neurons in culture and in vivo (Castillo-Carranza, et al, 2014a,Castillo-Carranza, et al, 2014b,Fa, et al, 2016,Gerson, et al, 2016,Lasagna-Reeves, et al, 2010,Tian, et al, 2013,Usenovic, et al, 2015).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, TrkA expression is under positive feedback from NGF (Holtzman et al, 1992; Li et al, 1995), and this pathway may be disrupted during the progression of dementia by reduced retrograde transport of cortical NGF to nbM consumer neurons (Mufson et al, 1995; Scott et al, 1995). While aggregated wild-type tau is a known inhibitor of anterograde fast axonal transport (Kanaan et al, 2012, 2011; LaPointe et al, 2009), there is some evidence to suggest that phosphorylation at S422 impairs retrograde transport, as well (Tiernan et al, 2016a). Thus, phosphorylation of tau at S422 and the resulting inhibition of retrograde transport may impair positive feedback from NGF leading to a loss of TrkA expression on the nbM neuronal cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, truncation of aspartic 421 facilitates tau aggregation and toxicity (García-Sierra et al, 2008) and phosphorylation at serine 422 could enhance SDS-stable dimer formation (Tiernan et al, 2016). …”
Section: Tau Primary Structurementioning
confidence: 99%